2017
DOI: 10.1093/icesjms/fsx106
|View full text |Cite
|
Sign up to set email alerts
|

Feeding by Calanus glacialis in a high arctic fjord: potential seasonal importance of alternative prey

Abstract: The copepod species Calanus glacialis is an important component of arctic marine food webs, where it is the numerically dominant zooplankton grazer and serves as a major prey item for fish, seabirds, and other predators. These copepods are typically considered to be phytoplanktivorous, although they are also known to feed on microzooplankton, and little is known about their diet in fall and winter. To investigate their feeding, C. glacialis gut contents were analyzed over an annual cycle in a seasonally ice co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 62 publications
6
45
0
Order By: Relevance
“…the signal, of which there is an overlap with ciliates that would be consumed as prey (Cleary et al, 2017). Second, winter studies regarding the abundance of likely prey sources have been infrequent across the Arctic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the signal, of which there is an overlap with ciliates that would be consumed as prey (Cleary et al, 2017). Second, winter studies regarding the abundance of likely prey sources have been infrequent across the Arctic.…”
Section: Discussionmentioning
confidence: 99%
“…Second, winter studies regarding the abundance of likely prey sources have been infrequent across the Arctic. In the lead up to the spring bloom (March), a relatively high proportion of chaetognaths have been observed in the gut contents of C. glacialis (Cleary et al, 2017). Chaetognaths are primarily predators of Calanus, but it is suggested that at this time of year, Calanus will predate upon eggs and juvenile stages of chaetognaths.…”
Section: Discussionmentioning
confidence: 99%
“…This trophic dynamic, termed the "mycoloop" (Kagami et al 2014), likely contributes to organic matter recycling and biological turnover within the euphotic zone, which confers a potential reduction of particulate organic matter export. The relevance of the Chytridiomycota to higher trophic levels appears to be seasonal, generally peaking during the spring phytoplankton bloom in high-latitude marine environments (Cleary et al 2017). Other zoosporic fungi include the Aphelida, Cryptomycota, Neocallimastigomycota, Olpidiomycota, and select members formerly within the Zygomycota, whose relative abundance in marine environments appears to be generally low, according to the limited number of DNA studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Screening of rRNA molecular barcodes and clone data has detected fungal communities comprised of an uncharacterized phylogenetic branch of Chytridiomycota (18) that appear to be important prey for Arctic zooplankton (19). These Arctic Chytridiomycota communities are primarily found with members of the Dikarya in sea ice, sediment (8,20) and in association with driftwood (21).…”
Section: Introductionmentioning
confidence: 99%